Aktivitas Antioksidan dan Penghambatan Xantin Oksidase Kulit Batang Songi (Dillenia serrata Thunb.): Antioxidant and Xanthine Oxidase Inhibitory Activity of Stem Bark of Songi (Dillenia serrata Thunb.) - Sabandar, Carla Wulandari; Jalil, Juriyati; Ahmat, Norizan; Aladdin, Nor-Ashila; Kamaruddin, Harni Sartika; Wahyuningrum, Retno (Universitas Tadulako, 2020)
Songi (Dillenia serrata) is a tree endemic to Southeast Sulawesi and its stem bark been used in folk medicine. Nonetheless, only a handful scientific knowledge regarding chemistry and biological activities has been investigated on the plant. The present study aimed to investigate the antioxidant and xanthine oxidase (XO) inhibitory activity of the stem bark of the plant. Methanol extract and organic fractions (petroleum ether, ethyl acetate, and methanol) of the dried powdered stem bark of songi were evaluated for phytochemical screening, total phenolic (TPC), total flavonoid contents (TFC), DPPH, FRAP, and XO in vitro assays. Flavonoids, tannins, terpenoids, steroids, and saponins present in the extract. TPC and TFC in extract were 59.2 mg GAE/g and 23.4 mg QE/g. The contents in organic fractions were in solvent-dependent manner (methanol>ethyl acetate>petroleum ether). Extract and fractions scavenged DPPH radicals (48.2–59.7%) at 100 μg/mL compared to ascorbic acid, trolox, and gallic acid (90.3–93.8%). FRAP values varied from 0.8–3.4 μg/μg equivalent trolox amount (quercetin and gallic acid were 25.7 dan 32.4 μg/μg, respectively). They also inhibited xanthine oxidase (15.3–50.3%) at 100 μg/mL (allopurinol, 98.2%). The study concluded the potential of methanol extract and organic fraction of the stem bark of songi, thus highlighted the prospect of songi to be used in herbal and drugs development from nature.